Patterns of care for non‐metastatic castration‐resistant prostate cancer: A population‐based study. Issue 5 (18th May 2022) - Malone, Shawn; Wallis, Christopher J. D.; Lee‐Ying, Richard; Basappa, Naveen S.; Cagiannos, Ilias; Hamilton, Robert J.; Fernandes, Ricardo; Ferrario, Cristiano; Gotto, Geoffrey T.; Morgan, Scott C.; Morash, Christopher; Niazi, Tamim; et al.
Abstract: Objectives: To describe patterns of practice of PSA testing and imaging for Ontario men receiving continuous ADT for the treatment of non‐metastatic castration‐resistant prostate cancer (nmCRPC). Patients and Methods: This was a retrospective, longitudinal, population‐based study of administrative health data from 2008 to 2019. Men 65 years and older receiving continuous androgen deprivation therapy (ADT) with documented CRPC were included. An administrative proxy definition was applied to capture patients with nmCRPC and excluded those with metastatic disease. Patients were indexed upon progression to CRPC and were followed until death or end of study period to assess frequency of monitoring with PSA tests and conventional imaging. A 2‐year look‐back window was used to assess patterns of care leading up to CRPC as well as baseline covariates. Results: At a median follow‐up of 40.1 months, 944 patients with nmCRPC were identified. Their median time from initiation of continuous ADT to CRPC was 26.0 months. 60.7% of patients had their PSA measured twice or fewer in the year prior to index, and 70.7% patients did not receive any imaging in the year following progression to CRPC. Throughout the study period, 921/944 (97.6%) patients with CRPC progressed to high‐risk (HR‐CRPC) with PSA doubling time ≤ 10 months, of which more than half received fewer than three PSA tests in the year prior to developing HR‐CRPC, and 30.9% received no imaging in the subsequent year. Conclusion: PSA testing and imaging studies are underutilized in a real‐world setting for the management of nmCRPC, including those at high risk of developing metastatic disease. Infrequent monitoring impedes proper risk stratification, disease staging and detection of treatment failure and/or metastases, thereby delaying the necessary treatment intensification with life‐prolonging therapies. Adherence to guideline recommendations and the importance of timely staging should be reinforced to optimize patient outcomes.